Review on Opinion Mining for Fully Fledged System - Asmita Dhokrat; Sunil Khillare; C. Namrata Mahender (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2016)
Humans communication is generally under the control of emotions and full of opinions. Emotions and their opinions plays an important role in thinking process of mind, influences the human actions too. Sentiment analysis is one of the ways to explore user’s opinion made on any social media and networking site for various commercial applications in number of fields. This paper takes into account the basis requirements of opinion mining to explore the present techniques used to develop a fully fledged system. Is highlights the opportunities or deployment and research of such systems. The available tools used for building such applications have even presented with their merits and limitations.